A multifunctional optical‐thermal logic gate sensor array based on ferroelectric BiFeO3 thin films - Li Wu; Yun Ji; Huiyu Dan; Chris R. Bowen; Ya Yang (InfoMat, 2023)
Abstract The growing need to process a diverse range of data has ignited effort in developing new multifunctional logic gate devices. In this article, we report a new form of all‐in‐one logic gate system that exploits the photoresponsivity of a self‐powered multifunctional BiFeO3 (BFO) sensor material. The BFO sensor can not only detect both light intensity and temperature, but it can also execute three common logic gates of “AND”, “OR”, and “NOT” by converting optical and thermal inputs into electrical output. The diverse functionality of the BFO logic gate sensor array utilizes the unique light‐and temperature‐controlled energy band structure and carrier behavior of the BFO material. To demonstrate the potential, a 3 × 3 logic gate sensor matrix is developed, which successfully detected light and temperature distributions, and accurately produced the three basic logic gate operations. This work provides a new route to construct highly integrated multifunctional electronic devices for the advancement of large sensing, communication, and computing operations.